Sphagnum fuscum Growth under Increasing Nitrogen Additions as Measured by the Cranked Wire Method, 2011-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). We measured linear growth using the cranked wire method (Clymo 1970). We set 30 cranked wires in each of the 21 study plots, with all wires placed in hummocks dominated by S. fuscum . Each year, from 2011 through 2015, we set cranked wires in May after the surface peat had thawed, and remeasured them at the end of the growing season (in late September or early October). Over all years and N treatments, S. fuscum linear growth averaged 2.3 ± 0.1 cm yr -1 . Linear growth was not affected by N addition in any of the five years.